2002
DOI: 10.1016/s1096-4959(01)00523-1
|View full text |Cite
|
Sign up to set email alerts
|

Social modulation of androgen levels in male teleost fish

Abstract: Androgens are classically thought of as the sex steroids controlling male reproduction. However, in recent years evidence has accumulated showing that androgens can also be affected by the interactions between conspecifics, suggesting reciprocal interactions between androgens and behaviour. These results have been interpreted as an adaptation for individuals to adjust their agonistic motivation and to cope with changes in their social environment. Thus, malemale interactions would stimulate the production of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(120 citation statements)
references
References 93 publications
5
114
1
Order By: Relevance
“…hauser and Oliveira, 2000; lizards: Thompson and Moore, 1992; but see Houck and Woodley, 1995;teleosts: Cardwell and Liley, 1991;Pankhurst and Barnett, 1993;Oliveira et al, 1996Oliveira et al, , 2001cOliveira et al, , 2002mammals: Cavigelli and Pereira, 2000;Nunes et al, 2000; but see Creel et al 1993). Only the change to extremely high paternal investment (i.e., paternal incubation among the altricial passerines) contributed to the evolution of different androgen response rates.…”
Section: Discussionmentioning
confidence: 99%
“…hauser and Oliveira, 2000; lizards: Thompson and Moore, 1992; but see Houck and Woodley, 1995;teleosts: Cardwell and Liley, 1991;Pankhurst and Barnett, 1993;Oliveira et al, 1996Oliveira et al, , 2001cOliveira et al, , 2002mammals: Cavigelli and Pereira, 2000;Nunes et al, 2000; but see Creel et al 1993). Only the change to extremely high paternal investment (i.e., paternal incubation among the altricial passerines) contributed to the evolution of different androgen response rates.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that social stimuli influence endocrine function in males and females of a variety of vertebrate species (see [13,108,136,180,185] for review). Most of these effects take place over a relatively long period (>days) and are therefore likely to influence genomic but not the more rapid non-genomic effects of steroids (fish: [145]; frog: [50]; birds: [119,183,184]; rat: [201]; rhesus monkey: [212]).…”
Section: Gonadal Production Of Steroidsmentioning
confidence: 99%
“…Furthermore, levels of 11-KT were positively correlated with received aggressive behavior. Since the individuals with high 11-KT levels were most active in territorial behavior this suggests that in fish, as well as in birds (e.g., Wingfield et al, 1990;Groothuis and Meeuwissen, 1992;Ros et al, 2002), a positive feedback mechanism is operative between external stimulation, androgens (specifically 11-KT) and aggressive behavior (see Oliveira et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The third prediction from the challenge hypothesis was that the levels of androgens should decrease during parental care (Wingfield et al, 1990) and in fish several studies have shown 11-KT levels to be lower in brooding than in nonbrooding males (see Oliveira et al, 2002 for a review). As already discussed above, we found that aggressive behavior and sexual behavior declined in animals that brooded eggs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation